Raman study of flash-lamp annealed aqueous Cu2ZnSnS4 nanocrystals - Havryliuk, Yevhenii; Selyshchev, Oleksandr; Valakh, Mykhailo; Raevskaya, Alexandra; Stroyuk, Oleksandr; Schmidt, Constance; Dzhagan, Volodymyr; Zahn, Dietrich R. T. (Beilstein Journal of Nanotechnology, 2019)
The effect of flash-lamp annealing (FLA) on the re-crystallization of thin films made of colloidal Cu2ZnSnS4 nanocrystals (NCs) is investigated by Raman spectroscopy. Unlike similar previous studies of NCs synthesized at high temperatures in organic solvents, NCs in this work, which have diameters as small as 2–6 nm, were synthesized under environmentally friendly conditions in aqueous solution using small molecules as stabilizers. We establish the range of FLA conditions providing an efficient re-crystallization in the thin film of NCs, while preserving their kesterite structure and improving their crystallinity remarkably. The formation of secondary phases at higher FLA power densities, as well as the dependence of the formation on the film thickness are also investigated. Importantly, no inert atmosphere for the FLA treatment of the NCs is required, which makes this technology even more suitable for mass production, in particular for printed thin films on flexible substrates.
Keywords: copper zinc tin sulfide Cu2ZnSnS4 (CZTS); CuS; Cu-Sn-S; kesterite; phonon; pulsed light crystallization; Raman spectroscopy; secondary phase; SnS